Utilizing of the Trello API Within the Development of a Monitoring Information System Recording of Project Activities Using a Website-Based Kanban System (Case Study : Electrical Project of PT. XYZ) - Chaerul, Rayhan Alya; Putra, Widhy Hayuhardhika Nugraha; Hanggara, Buce Trias (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
One of the units of the company which is engaged in electricity handles many electrical large projects. The current condition of recording project activities that is still done manually and is not centralized has become difficulties in searching for data when needed. Job targets that also cannot be monitored create difficulties in management. Therefore, an effective and efficient monitoring information system for recording project activities is required so as to facilitate the management of monitoring data projects and data retrieval. The system development process using the prototyping method is implemented on a website basis by utilizing the Kanban system in managing work items. The Trello API is used to retrieve project data along with the use of the Kanban system in Trello to maintain data security which can only be managed by the project manager. System development is carried out through the stages of problem identification, literature study, needs analysis, design with Unified Modeling Language, and implementation using Laravel as a framework. Functional testing of the system with Blackbox testing gets 100% indicating the system is in accordance with the requirements specifications. Usability testing using the System Usability Scale gets a value of 84 in the acceptable system category. Responsive testing is conducted with the results of the interface meets various screen sizes and orientations. The compatibility testing implementation shows the system works well with various browsers.